Determinants of Vertical Integration: Investment Efficiency, Product Differentiation and Firm Size - Yamawake, Toshiyuki; Yamoto, Shigetsune; Goi, Hoe Chin; Lee, Dong-Joon (Scientific Research, 2018)
This study examines the determinants of Merger and Acquisition (M & A) when manufacturing firms integrate with retailing firms. We examine a manufacturing duopoly in which each upstream firm sells the output to its exclusive retailing firm. In sequence of the timing of game, the strategic variables are set as Research and Development (R & D) investment, wholesale price by manufacturing firms and sales volume by retailing firms. The study concludes that degree of investment efficiency, product differentiation, and market size play important roles in vertical integration. Our conclusion shows that if product differentiation becomes greater, the vertical integration increases. Secondly, if the market size becomes larger, the vertical integration increases. Thirdly, the vertical integration increases when investment efficiency becomes higher. Our theoretical findings are also supported by the empirical results with the listed Japanese company data from 1996 to 2016.
Keywords: Investment Efficiency; Product Differentiation; Market Size; Vertical Integration